All Round View - Khan, Imran (London Chatto & Windus, 1988)
A self portrait of Imran Khan, now 35, one of cricket's greatest all-rounders and retiring captain of Pakistan's team. The book reveals much about his life, the game of cricket, and the changes which have taken place not only in that sport but in the man himself.
Include Illustrations and Index.
Keywords: Cricket players -- Khan, Imran -- Pakistan